The Role Of Local Original Income (PAD) And The Level Of Community Welfare In Stimulating The Rate Of Economic Growth In Bojonegoro Regency In 2014-2024 - Febrianti, Elika (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to analyze the role of Locally Generated Revenue (PAD) and community welfare in driving economic growth in Bojonegoro Regency. PAD is one of the main sources of financing for regional development, while community welfare is an indicator of the success of sustainable development. The method used in this study is a quantitative approach with secondary data analysis obtained from official publications of the Central Statistics Agency and related agencies in Bojonegoro Regency over the past five years. The results show that PAD has a positive influence on regional economic growth, primarily through increased development spending. On the other hand, the level of community welfare—as measured by indicators of poverty, unemployment, and the human development index (HDI)—also contributes significantly to the dynamics of economic growth. These findings emphasize the importance of synergy between optimizing PAD and improving community welfare in creating inclusive and sustainable economic growth at the local level.